Chronic kidney disease and risk of postoperative cardiovascular events in elderly patients receiving hip fracture surgery. Issue 2 (February 2022) - Jiang, Yu; Luo, Yan; Li, Jia; Jiang, Yuheng; Zhao, Jingxin; Gu, Siqi; Li, Ping; Zhang, Licheng; Yin, Pengbin; Lyu, Houchen; Tang, Peifu
Highlights: Chronic kidney disease (CKD) is a common comorbidity, accounting for about 18% of all hip fracture patients over 65 years old. Elderly patients with CKD are at highly increased risk of cardiovascular events following hip fracture surgery. Preoperative cardiovascular risk assessment and corresponding preventive measures should be given to this vulnerable population. Abstract: Introduction: The long-term risk of cardiovascular events caused by chronic kidney disease (CKD) is well described in the general population. Less is known concerning the risk of postoperative cardiovascular events in geriatric hip fracture patients with CKD. Methods: This study involved patients at least 65 years of age who received surgery for acute hip fracture between January 2000 and April 2016. We identified CKD patients with a baseline diagnosis of CKD or an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m 2 at admission. Each CKD patient was matched, for age, gender, fracture type, and year of admission, with 4 control non-CKD patients. The primary endpoint was a compositepostoperative cardiovascular events, including pulmonary embolism, angina pectoris, myocardial infarction, heart failure, arrhythmia, stroke, and death. Conditional logistic regression was used to evaluate the association between CKD and the outcome after adjusting for potential confounders including age, gender, fracture type, body mass index, preexisting comorbidities, history of cardiovascular events, and the Charlson Comorbidity Index (CCI). Results: Three hundred and seventy-five CKD patients were matched with 1, 438 non-CKD patients. The mean age of the CKD patients was 81.9 ± 7.0 (mean ± SD), 69.9% were females, and 59.2% had an intertrochanteric fracture. Compared to non-CKD patients, CKD patients had a higher proportion of preexisting comorbidities, including hypertension, coronary heart disease, heart failure, and type 2 diabetes (all p < 0.05). The risk of postoperative cardiovascular events was 125.3 per 1000 persons (95%CI, 91.8–158.8) in CKD patients and 64.7 per 1000 persons (95%CI, 52.0–77.4) in non-CKD patients. A 1.96-fold risk of cardiovascular events after hip fracture surgery was found in CKD patients than those without CKD (adjusted OR, 1.96; 95%CI, 1.23–3.12). Conclusion: Patients with CKD were more likely to have cardiovascular events after hip fracture surgery than those without CKD. Appropriate preoperative cardiovascular risk assessment and corresponding preventive and therapeutic measures should be given to this vulnerable population to mitigate such complications.